Activation of eIF4E‐binding‐protein‐1 rescues mTORC1‐induced sarcopenia by expanding lysosomal degradation capacity. Issue 1 (17th November 2022) - Crombie, Elisa M.; Kim, Seonyoung; Adamson, Stuart; Dong, Han; Lu, Tzu‐Chiao; Wu, Yiju; Wu, Yajun; Levy, Yotam; Stimple, Nolan; Lam, Wing Moon R.; Hey, Hwee Weng D.; Withers, Dominic J.; et al.
Abstract: Background: Chronic mTORC1 activation in skeletal muscle is linked with age‐associated loss of muscle mass and strength, known as sarcopenia. Genetic activation of mTORC1 by conditionally ablating mTORC1 upstream inhibitor TSC1 in skeletal muscle accelerates sarcopenia development in adult mice. Conversely, genetic suppression of mTORC1 downstream effectors of protein synthesis delays sarcopenia in natural aging mice. mTORC1 promotes protein synthesis by activating ribosomal protein S6 kinases (S6Ks) and inhibiting eIF4E‐binding proteins (4EBPs). Whole‐body knockout of S6K1 or muscle‐specific over‐expression of a 4EBP1 mutant transgene (4EBP1mt), which is resistant to mTORC1‐mediated inhibition, ameliorates muscle loss with age and preserves muscle function by enhancing mitochondria activities, despite both transgenic mice showing retarded muscle growth at a young age. Why repression of mTORC1‐mediated protein synthesis can mitigate progressive muscle atrophy and dysfunction with age remains unclear. Methods: Mice with myofiber‐specific knockout of TSC1 (TSC1mKO), in which mTORC1 is hyperactivated in fully differentiated myofibers, were used as a mouse model of sarcopenia. To elucidate the role of mTORC1‐mediated protein synthesis in regulating muscle mass and physiology, we bred the 4EBP1mt transgene or S6k1 floxed mice into the TSC1mKO mouse background to generate 4EBP1mt‐TSC1mKO or S6K1‐TSC1mKO mice, respectively. Functional and molecular analyses were performed to assess their role in sarcopenia development. Results: Here, we show that 4EBP1mt‐TSC1mKO, but not S6K1‐TSC1mKO, preserved muscle mass (36.7% increase compared with TSC1mKO, P  < 0.001) and strength (36.8% increase compared with TSC1mKO, P  < 0.01) at the level of control mice. Mechanistically, 4EBP1 activation suppressed aberrant protein synthesis (two‐fold reduction compared with TSC1mKO, P  < 0.05) and restored autophagy flux without relieving mTORC1‐mediated inhibition of ULK1, an upstream activator of autophagosome initiation. We discovered a previously unidentified phenotype of lysosomal failure in TSC1mKO mouse muscle, in which the lysosomal defect was also conserved in the naturally aged mouse muscle, whereas 4EBP1 activation enhanced lysosomal protease activities to compensate for impaired autophagy induced by mTORC1 hyperactivity. Consequently, 4EBP1 activation relieved oxidative stress to prevent toxic aggregate accumulation (0.5‐fold reduction compared with TSC1mKO, P  < 0.05) in muscle and restored mitochondrial homeostasis and function. Conclusions: We identify 4EBP1 as a communication hub coordinating protein synthesis and degradation to protect proteostasis, revealing therapeutic potential for activating lysosomal degradation to mitigate sarcopenia.